2012
DOI: 10.1021/la301311m
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Reflectivity Characterization of the Photoacid Reaction-Diffusion Latent and Developed Images of Molecular Resists for Extreme Ultraviolet Lithography

Abstract: Lithographic feature size requirements have approached a few radius of gyration of photoresist polymers used in thin-film patterning. Furthermore, the feature dimensions are commensurate with the photoacid diffusion length that defines the underlying latent image. Smaller imaging building blocks may enable reduced feature sizes; however, resolution limits are also dependent upon the spatial extent of the photoacid-catalyzed reaction diffusion front and subsequent dissolution mechanism. The reaction-diffusion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…A few studies have been able to measure acid diffusivity using semidirect methods. One approach detected the time required for the acid to diffuse through a polymer film of known thickness, and then used Fick’s second law to estimate the diffusivity. , Another approach employed neutron reflectivity to record the shape of the reaction front, and then extracted the diffusivity using a model of Fickian acid transport coupled to fast deprotection and acid trapping. However, indirect methods to examine acid diffusion and acid loss are more prevalent in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been able to measure acid diffusivity using semidirect methods. One approach detected the time required for the acid to diffuse through a polymer film of known thickness, and then used Fick’s second law to estimate the diffusivity. , Another approach employed neutron reflectivity to record the shape of the reaction front, and then extracted the diffusivity using a model of Fickian acid transport coupled to fast deprotection and acid trapping. However, indirect methods to examine acid diffusion and acid loss are more prevalent in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…We further optimized the lithographic performance of the thiol–ene resist systems under a variety of conditions including reduced exposure doses, adjusted the monomer concentrations and ratios of alkenes to thiols, and selected the carboxyl ligand developers (e.g., acetic acid/acetone mixture) (Figure S16). The photoelectron/radical diffusion process, in contrast to photoacid diffusion, makes non-negligible contributions to the residue of unexposed areas or bridges, especially for highly sensitive free radical-type systems. , The deep-UV exposure results (Figure e) indicated that the residual issue was significantly improved by the addition of adequate hydroquinone (2 wt % to monomers, with all other conditions identical). After being exposed to a dose of 10 mJ cm –2 and developed in toluene for 30 s, clear 1:1 L/S dense patterns were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(4‐hydroxystyrene)s (PHOSTs) are widely used in many fields such as drug therapy agents, 1 drug delivery, 2 self‐healing materials 3,4 and photoresists 5‐7 . When PHOSTs are used as photoresists resin for KrF and EUV photolithography process, 6,7 the pattern resolution is largely limited by molecular weight distribution (MWD), 8‐11 with critical dimension of the device features extends below 22 nm. Living or quasiliving cationic polymerization (LCP or QLCP) has offered a strategy for the macromolecular design with alkyl vinyl ethers, 12 isobutene, 13 styrene and its derivatives 14‐19 .…”
Section: Introductionmentioning
confidence: 99%